Ischemic preconditioning induces cortical microglial proliferation and a transcriptomic program of robust cell cycle activation. Issue 1 (17th August 2019) - McDonough, Ashley; Noor, Shahani; Lee, Richard V.; Dodge, Ryan; Strosnider, James S.; Shen, Jasmine; Davidson, Stephanie; Möller, Thomas; Garden, Gwenn A.; Weinstein, Jonathan R.
Abstract: Ischemic preconditioning (IPC) is an experimental phenomenon in which a subthreshold ischemic insult applied to the brain reduces damage caused by a subsequent more severe ischemic episode. Identifying key molecular and cellular mediators of IPC will provide critical information needed to develop novel therapies for stroke. Here we report that the transcriptomic response of acutely isolated preconditioned cortical microglia is dominated by marked upregulation of genes involved in cell cycle activation and cellular proliferation. Notably, this transcriptional response occurs in the absence of cortical infarction. We employed ex vivo flow cytometry, immunofluorescent microscopy, and quantitative stereology methods on brain tissue to evaluate microglia proliferation following IPC. Using cellular colocalization of microglial (Iba1) and proliferation (Ki67 and BrdU) markers, we observed a localized increase in the number of microglia and proliferating microglia within the preconditioned hemicortex at 72, but not 24, hours post‐IPC. Our quantification demonstrated that the IPC‐induced increase in total microglia was due entirely to proliferation. Furthermore, microglia in the preconditioned hemisphere had altered morphology and increased soma volumes, indicative of an activated phenotype. Using transgenic mouse models with either fractalkine receptor (CX3CR1)‐haploinsufficiency or systemic type I interferon signaling loss, we determined that microglial proliferation after IPC is dependent on fractalkine signaling but independent of type I interferon signaling. These findings suggest there are multiple distinct targetable signaling pathways in microglia, including CX3CR1‐dependent proliferation that may be involved in IPC‐mediated protection. Main Points: Microglia‐specific transcriptomic and immunohistological data highlights a proliferative response initiated by ischemic preconditioning. This response is dependent on the fractalkine receptor CX3CR1 and independent of type 1 interferon signaling.